Hacking humanitarians: Defining the cyber perimeter and developing a cyber security strategy for international humanitarian organizations in digital transformation. (April 2020) - Marelli, Massimo
Abstract: Digitalization and new technologies have an increasingly important role in today's humanitarian activities. As humanitarian organizations become more active in and reliant on new and digital technologies, they evolve from being simple bystanders to being fully fledged stakeholders in cyberspace, vulnerable to adverse cyber operations that could impact on their capacity to protect and assist people affected by armed conflict or other situations of violence. This shift makes it essential for humanitarian organizations to understand and properly map their resulting cyber perimeter. Humanitarian organizations can protect themselves and their activities by devising appropriate cyber strategies for the digital environment. Clearly defining the digital boundaries within which they carry out operations lays the groundwork for humanitarian organizations to develop a strategy to support and protect humanitarian action in the digital environment, channel available resources to where they are most needed, and understand the areas in which their operational dialogue and working modalities need to be adapted for cyberspace. The purpose of this article is to identify the unique problems facing international humanitarian organizations operating in cyberspace and to suggest ways to address them. More specifically, the article identifies the key elements that an international humanitarian organization should consider in developing a cyber security strategy. Throughout, the International Committee of the Red Cross and its specificities are used as an example to illustrate the problems identified and the possible ways to address them.